A new species of Sapadrama Hancock & Marshall (Diptera: Tephritidae) from China and an updated key to the known species - Chen, Xiaolin; Wang, Yong (Zootaxa, 2023)
One new tephritid species, Sapadrama nigra sp. nov., from China is described and illustrated. In addition, the genus, Sapadrama Hancock & Marshall, 2012 and the species, Sapadrama citrina Hancock & Marshall, 2012 are reported from China for the first time. A key to the known species of this genus is provided, and the relationship of Sapadrama with Cyaforma Wang, 1989 and Ortalotrypeta Hendel, 1927 is briefly discussed. Moreover, some biological notes of this genus are reported.